Perancangan Verifikasi Menggunakan Garis-Garis Telapak Tangan - Wijaya, Novan; Irsyad, Hafiz; Taqwiym, Akhsani (Teknomatika, 2017)
There are two types of recognition systems namely verification and identification. The verification system aims to accept or deny an identity claimed by a person, while the identification system is solving one's identity. The design of verification of palm lines is a process of matching the palm of the hand which will later be tested with a palm that is claimed or stored in the database. The palm of the hand is a relatively new biometric, which has unique characteristics in the form of palm lines and is stable. System design will use use case, class analysis, class diagram, sequence diagram, and interface design. This design is expected to be an alternative in the pre-existing verification process.Keywords-design, identification, palms.